Mycological and toxicological analysis of peanuts and derivatives - Robson Lima; Douglas Melquíades Fortunato de Oliveira; Luciana Rosa Alves Rufino; Marcelo Fabiano Gomes Boriolo; Alessandra Cristina Pupin Silvério; José Antônio Dias Garcia; João Evangelista Fiorini; Nelma Mello Silva Oliveira (São Paulo State University (UNESP), 2012)
The filamentous fungi Aspergillus flavus, Aspergillus parasiticus and Aspergillus nomius produce toxins, which are secondary metabolites called aflatoxins. These toxin-producing species grow rapidly on peanuts and cereals in favorable conditions of temperature and humidity. Their toxins can either cause acute effects, and even be lethal or accumulate in the organism, resulting in liver cancer in the long term. Based on the health risks of aflatoxins in food, a research was conducted on peanuts and derivatives sold in Alfenas, MG, Brazil, to evaluate the presence of Aspergillus sp. and aflatoxins. The samples were randomly collected at "popular stores", from November 2008 to May 2009, to assess the occurrence of aflatoxins B 1, B2, G1 and G2 by thin layer chromatography (TLC). The mycological analysis revealed the presence of fungi in 50% of the samples: Penicillium sp. (53.85%), A. flavus (19.23%), A. niger (15.38%) and A. fumigatus (11.54%), and 63.64% of these showed the presence of aflatoxins : B1 (43.14%), B2 (25.49%), G1 (23.53%) and G2 (7.84%). It is concluded that the results reported here are a cause for concern, given the harmfulness of these cumulative and carcinogenic toxins.